Association between hs-CRP/HDL with type 2 diabetes mellitus in middle-aged and elderly people: a cross-sectional study from CHARLS - Jiang, Yan; Yu, Jiali (Frontiers in Endocrinology, 2025)
BackgroundResearch into the relationship between the ratio of high-sensitivity C-reactive protein (hs-CRP) and high-density lipoprotein cholesterol (HDL-C) concerning type 2 diabetes mellitus (T2DM) is still scarce. The hs-CRP/HDL ratio could be an important biomarker for evaluating the risk of developing diabetes. This study primarily aims to investigate the association between hs-CRP/HDL ratios and the incidence of T2DM within a defined population.MethodsThis analysis was conducted using data from 9,381 participants aged 45 and older, obtained during the 2011 wave of the China Health and Retirement Longitudinal Study (CHARLS). The study evaluated the association between the hs-CRP/HDL ratio and the risk of developing type 2 diabetes mellitus (T2DM) employing multivariate logistic regression, subgroup analyses, smooth curve fitting, and threshold effect analysis.ResultsThe overall prevalence of T2DM within the study population was found to be 16.3%, with 46.1% of cases occurring in men and 53.9% in women. Participants diagnosed with T2DM demonstrated a mean hs-CRP/HDL ratio that was 1.2 times higher than that of individuals without diabetes. The adjusted odds ratio (OR) for T2DM associated with hs-CRP/HDL levels was determined to be 0.75 (95% CI: 0.64–0.87). Additionally, a significant interaction was identified between hs-CRP/HDL ratios and variables such as sex and smoking in relation to T2DM risk (P < 0.05). Further subgroup analyses examining factors like age, education, marital status, hukou status, and drinking habits did not reveal any significant interactions (all P values for interaction were >0.05).ConclusionsThe results highlight a robust association between the hs-CRP/HDL ratio and the likelihood of developing T2DM, indicating its potential as a predictive biomarker for the condition. Additional research is required to clarify the relationship between hs-CRP/HDL ratios and the incidence of T2DM.